Nazratul Husna – Recipient of Dimension Bid Sdn. Bhd. Industrial Award - Shalfarina, Shahriman (2018)
The experience gained when she was a participant in a student exchange programme to Turkey two years ago provided the impetus for Nazratul Husna Yatim Selamat, to complete her studies with flying colours.